Efficacy of tranilast in preventing exacerbating cardiac function and death from heart failure in muscular dystrophy patients with advanced-stage heart failure: a single-arm, open-label, multicenter study - Tsuyoshi Matsumura; Takayasu Fukudome; Yasufumi Motoyoshi; Akinori Nakamura; Satoshi Kuru; Kazuhiko Segawa; Ruriko Kitao; Chigusa Watanabe; Takuhisa Tamura; Toshiaki Takahashi; Hiroya Hashimoto; Masahiro Sekimizu; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Transient receptor potential cation channel subfamily V member 2 (TRPV2) functions as a stretch-sensitive calcium channel, with overexpression in the sarcolemma of skeletal and cardiac myocytes leading to detrimental calcium influx and triggering muscle degeneration. In our previous pilot study, we showed that tranilast, a TRPV2 inhibitor, reduced brain natriuretic peptide levels in two patients with muscular dystrophy and advanced heart failure. Building on this, we performed a single-arm, open-label, multicenter study herein to evaluate the safety and efficacy of tranilast in the treatment of advanced heart failure in patients with muscular dystrophy. Results This study involved 18 patients with muscular dystrophy who had brain natriuretic peptide levels > 100 pg/mL, despite receiving standard cardioprotective therapy. Tranilast was administered orally at a dose of 100 mg three times daily. Over the short-term period (28 weeks), the primary endpoint of change ratio in the logarithm of brain natriuretic peptide level from baseline to 28 weeks was not significant in the full analysis set but was lower in the per set protocol compared with data from a previous beta-blocker treatment study. All 15 patients who completed the short-term treatment consented to be enrolled in long-term therapy for an additional 116 weeks. After all participants completed the long-term treatment, we analyzed all data. TRPV2 expression on the peripheral blood mononuclear cell surfaces decreased throughout the study period, confirming that the TRPV2 inhibitory effect of tranilast was maintained over time. Despite the presence of progressive disease, cardiac indices such as brain natriuretic peptide level, human atrial natriuretic peptide level, and fractional shortening, remained stable, and only brain natriuretic peptide levels at 144 weeks showed significant changes. The survival rate was 80.7%, and no cardiac deaths were reported. Regarding safety, no serious adverse events associated with tranilast were noted, except for recurrent diarrhea during the short-term period in one case. Conclusions The findings suggest that tranilast can inhibit TRPV2 expression for an extended period and is effective in preventing the worsening of cardiac function and subsequent death from heart failure. Clinical trial registration details The study was registered in the UMIN Clinical Trials Registry (UMIN-CTR: UMIN000031965, URL: http://www.umin.ac.jp/ctr/ ) [March 30, 2018] and the Japan Registry of Clinical Trials (jRCT, registration number: jRCTs031180038, URL: https://jrct.niph.go.jp/ ) [November 12, 2021]. Patient registration was initiated on December 19, 2018.